Preparation and characterization of activated carbon from desiccated coconut residue by potassium hydroxide - Yahya M.A.; Al-Qodah Z.; Ngah C.W.Z.C.W.; Hashim M.A. (Chemical Publishing Co., 2024)
Indexed by Scopus